2021
DOI: 10.1186/s13722-021-00268-0
|View full text |Cite
|
Sign up to set email alerts
|

Project MIMIC (Maximizing Implementation of Motivational Incentives in Clinics): A cluster-randomized type 3 hybrid effectiveness-implementation trial

Abstract: Background Opioid-related overdoses and harms have been declared a public health emergency in the United States, highlighting an urgent need to implement evidence-based treatments. Contingency management (CM) is one of the most effective behavioral interventions when delivered in combination with medication for opioid use disorder, but its implementation in opioid treatment programs is woefully limited. Project MIMIC (Maximizing Implementation of Motivational Incentives in Clinics) was funded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 77 publications
(84 reference statements)
1
13
0
Order By: Relevance
“…For example, contingency management training interventions could be adapted to support rural primary care practitioners. 31,32 People who reported using both methamphetamine and opioids also reported greater challenges in accessing substance use treatment, which is consistent with a systematic review 33 of 39 studies that found that methamphetamine use was negatively associated with receipt of medications for opioid use disorder and retention in treatment. Our study findings suggest that access to treatment might be particularly challenging for people living in rural communities that have fewer methadone programs, 14 buprenorphine providers, 15 and behavioral health services, 13 an essential component of methamphetamine use disorder treatment, for which no medications have been approved, than urban areas.…”
Section: Jama Network Open | Substance Use and Addictionsupporting
confidence: 73%
See 1 more Smart Citation
“…For example, contingency management training interventions could be adapted to support rural primary care practitioners. 31,32 People who reported using both methamphetamine and opioids also reported greater challenges in accessing substance use treatment, which is consistent with a systematic review 33 of 39 studies that found that methamphetamine use was negatively associated with receipt of medications for opioid use disorder and retention in treatment. Our study findings suggest that access to treatment might be particularly challenging for people living in rural communities that have fewer methadone programs, 14 buprenorphine providers, 15 and behavioral health services, 13 an essential component of methamphetamine use disorder treatment, for which no medications have been approved, than urban areas.…”
Section: Jama Network Open | Substance Use and Addictionsupporting
confidence: 73%
“…Educational interventions are needed to train primary care practitioners—who are key providers of opioid use disorder treatment in the rural US—how to better address methamphetamine use among people who use opioids. For example, contingency management training interventions could be adapted to support rural primary care practitioners …”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review of the parent trial, project MIMIC (maximizing implementation of motivational incentives in clinics), is available elsewhere (Becker et al, 2021 ). Briefly, it is a type 3 hybrid trial (Curran et al, 2012 ) with cluster-randomization of New England OTPs receiving one of two sets of implementation strategies: (1) an addiction technology transfer center (ATTC) approach, consisting of workshop training followed by performance feedback and monthly facilitation calls (Squires et al, 2008 ); or (2) an enhanced ATTC approach, with the ATTC components augmented by implementation and sustainment facilitation (Garner et al, 2017 ) and pay-for-performance incentives (Garner et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the expense of virtual trainings is not well-documented, nor does extant literature clearly address comparative cost-effectiveness of in-person and virtual workshop training for EBPs like CM. Consequently, the current work seeks to address these gaps in the EBP training literature, using data from an ongoing, multi-cohort trial (Becker et al, 2021 ) that examines implementation of prize-based CM in opioid treatment programs (OTPs). In this trial, OTP staff participate in initial workshop training and complete a role-play as a post-training assessment of fidelity.…”
Section: Introductionmentioning
confidence: 99%
“…Based on my experience with the effectivenessimplementation HTD, which beyond the three innovative applications highlighted in the prior section includes two Type 3 effectiveness-implementation hybrid trials (20,21), and a Type 1 effectiveness-implementation hybrid trial (22), I would attest that the first two HTD types (Type 1, Type 2) can help improve the speed and efficiency of translation, especially as part of translational research focused on the T2 (clinical research) stage of the translational research spectrum (23). Additionally, I would attest that the third type (Type 3) can help improve the speed and efficiency of translation, especially as part of translational research focused on the T3 (clinical implementation) stage (23).…”
Section: The Diesel Hybrid Trial Designmentioning
confidence: 99%